Mobile money: a gateway to achieving financial inclusion in Ghana - Kodom, M.; Steel, W.F.; Ackah, C.; Bokpin, G.A. (Enterprise Development and Microfinance, 2022)
While emerging studies on mobile financial inclusion have focused on the factors driving the adoption of mobile money, little evidence exists on how the service is facilitating the use of formal financial services. Using the World Bank Findex data, we estimate the effect of mobile money adoption on the use of formal accounts, savings, and credit in Ghana. The results of the recursive bivariate probit analysis showed a significant symbiotic relationship between mobile money adoption and the probability of operating a formal account. Mobile money adoption has a positive effect on savings and access to credit but does not affect the avenues to savings and obtaining credit, respectively. Mobile money users save in their wallet and obtain microcredit through the mobile money platform but not through formal channels. These findings reinforce the hypothesis that mobile money is the surest financial tool for achieving universal financial inclusion in developing countries.
Research Article
Keywords: mobile money; financial inclusion; savings